The Mind and Body are Connected with each other through Psycho-Neuro Endocrine and Reticulo-Endothelial System (Advancements in Homeopathic Research, 2022)
PNEI- PSYCHONEUROIMMUNOENDOCRINO LOGY is the study of the interaction between psychological, neural, endocrine and immunological responses- which was first described in 1936. There is a unity of mind and body (reflected in term mind and body medicine); and psychological factors must be taken into account when considering all disease states. Although most physical disorders are influenced by stress, conflict, or generalized anxiety, some disorders are more affected than others. The concept of PNEI system propose that stressful event triggers cognitive and affective responses which, in turn induce sympathetic nervous system and endocrine changes and these ultimately impair immune function.The present review provides an overview of the fundamental literature on PNEI and its interaction with chronic low grade cellular inflammation processes, Hormetic processes, longevity with reference to resilience as a key factor in natural/pathologic evolution of aging. And consequently with the Homoeopathic standpoint where Dynamic, Functional and Structural plane been corelated.
Keywords: Psychoneuroimmunoendocrinology; Psychoneuroimmunology; Stress; Psychiatry